Printable cellulose-based electroconductive composites for sensing elements in paper electronics. (27th March 2017) - Barras, R; Cunha, I; Gaspar, D; Fortunato, E; Martins, R; Pereira, L
Abstract: Conductive flexible hydrogel composites were printed on paper substrates using a functional ink, which was designed and formulated for screen-printing. The inks were prepared using abundant and eco-friendly materials by blending carbon fibers into the matrix of a water-soluble cellulose derivative, carboxymethyl cellulose. For an optimal concentration of carbon fibers (10 wt.%), the printed patterns exhibit a sheet resistance of around 300 Ω/sq without any post-printing annealing process. The resistance of the screen-printed hydrogel patterns is sensitive to variations of relative air humidity through moisture adsorption and swelling of the cellulosic matrix surrounding the carbon fibers. It was found that the sensitivity to temperature and humidity can be triggered by drying the printed patterns at 120 °C. A negative temperature coefficient thermistor with a sensitivity of 0.079 °C −1 at 25 °C and a hygristor, where a variation in the RH from 10% to 60% increases the resistance by 15 times, were screen-printed on paper using the formulated cellulose/carbon fibers based ink.